A self-assessment tool for social responsibility in higher education. Reporting on a national policy development process in Portugal - Fonseca, Susana; Lobo Fernandes, Joana (International journal of sustainability in higher education, 2022)
Purpose Providing higher education institutions (HEIs) with a tool for self-assessing their social responsibility (SR) that generates the information and knowledge necessary to a strategic approach to adopting the Green Paper recommendations about the SR of HEIs. Setting out the collaborative policy development process to construct the tool “Indicators of SR of HEIs” (ISRHEI). Design/methodology/approach After a literature review, including self-assessment (SA) tools and leading guidelines, a working group of 24 Portuguese HEIs was created to co-construct the ISRHEI tool, which was then subject to validation in a pilot study. Findings There are 34 indicators in the ISRHEI tool, structured by sequential levels according to the HEI alignment with SR (policies, procedures, practices and monitoring along a strategic continuum) hoping to achieve impacts on the organisational, educational, cognitive and social level. Originality/value This is an innovative and national policy development process for SR in Portugal. It gives insights into guiding documents, SA indicators for SR and the process of developing consensus on this topic amongst 24 HEIs in Portugal. The ISRHEI tool is tailored to the specific characteristics and level of development of HEIs.